2020
DOI: 10.1089/thy.2019.0535
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Parameters Are More Likely to Be Associated with Thyroid Hormone Levels than with Thyrotropin Levels: A Systematic Review and Meta-Analysis

Abstract: Background: Though the functional states of other endocrine systems are not defined on the basis of levels of controlling hormones, the assessment of thyroid function is based on levels of the controlling hormone thyrotropin (TSH). We, therefore, addressed the question as to whether levels of thyroid hormones [free thyroxine (fT4), total triiodothyronine (TT3)/free triiodothyronine (fT3)], or TSH levels, within and beyond the reference ranges, provide the better guide to the range of clinical parameters associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 125 publications
(318 reference statements)
5
63
1
3
Order By: Relevance
“…Interestingly, in their recent meta-analysis of 58 studies, Fitzgerald et al demonstrated thyroid-hormone levels (FT 4 , TT 3 /FT 3 ) had a stronger correlation with clinical parameters than TSH levels, and recommended reconsidering the current practice of a TSH-based approach to defining thyroid function. 23 Our study has a few limitations: its retrospective design; the fact that it was a single-center study conducted at an academic center; the predominantly Caucasian study population; inpatient services, such as pediatrics, obstetrics-gynecology, and surgery, were not included; we did not research clinical features linked to the ordering of TFTs; and lastly we did not analyze providers' reasoning behind the ordering of the thyroid assays and arrival at a diagnosis. However, our study adds to the growing literature demonstrating low yield of thyroid labs in the inpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in their recent meta-analysis of 58 studies, Fitzgerald et al demonstrated thyroid-hormone levels (FT 4 , TT 3 /FT 3 ) had a stronger correlation with clinical parameters than TSH levels, and recommended reconsidering the current practice of a TSH-based approach to defining thyroid function. 23 Our study has a few limitations: its retrospective design; the fact that it was a single-center study conducted at an academic center; the predominantly Caucasian study population; inpatient services, such as pediatrics, obstetrics-gynecology, and surgery, were not included; we did not research clinical features linked to the ordering of TFTs; and lastly we did not analyze providers' reasoning behind the ordering of the thyroid assays and arrival at a diagnosis. However, our study adds to the growing literature demonstrating low yield of thyroid labs in the inpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…The general finding that free thyroid hormones are largely associated with RHR whereas TSH is not, is not surprising as TSH is not a perfect mirror of thyroid hormone status, whereas FT3 and FT4 are the hormones of interest that may also exert some rapid effects that can either be thyroid hormone receptor dependent or independent [18,19]. A meta-analysis has also confirmed that thyroid hormones are better correlated to various clinical parameters than TSH concentrations [20]. In line with this, a systematic review and individual participant meta-analysis in euthyroid individuals documented that FT4 but not TSH is associated with increased risk of incident atrial fibrillation [21].…”
Section: Discussionmentioning
confidence: 97%
“…Hence, a dual etiology may explain the findings of previous studies. To resolve this ambiguity, measurements of peripheral thyroid hormones are required (11) and should be integrated into future studies-not only for the selection of subjects but also for functional assessment (10,57,58). Calculated parameters providing biomarkers for the set point of thyroid homeostasis and peripheral hormone metabolism may provide additional insights, especially in the setting of clinical trials (41).…”
Section: Discussionmentioning
confidence: 99%
“…At least in elderly subjects, the benefits of levothyroxine substitution are questionable (5). While increased and high-normal free thyroxine (FT4) concentration is a well-established risk factor for malignant arrhythmia and sudden cardiac death (6,7), the association between thyrotropin (TSH) concentration and cardiovascular mortality is less well understood (8)(9)(10)(11). Studies reported either no relation at all (12,13) or a rather complex Ushaped association (14,15), as has been shown in a recent population study based on the large NHANES datasets (16).…”
Section: Introductionmentioning
confidence: 99%